The expression of secondary sexual characteristics in recruit- and repeat-spawning farmed and wild Atlantic cod (Gadus morhua) - Skjæraasen, J E; Meager, J J; Karlsen, Ø (ICES Journal of Marine Science, 2008)
We examined the expression of the two known secondary sexual characteristics of Atlantic cod, the pelvic fin and the drumming muscle, in farmed and wild cod stemming from the same population. Farmed and wild males had longer pelvic fins and larger drumming muscles than females, but wild cod had longer fins than farmed cod. The size of the drumming muscle of males was similar among wild and farmed cod, but farmed females had smaller muscles than their wild counterparts. Repeat-spawning wild males tended to invest less in drumming-muscle mass and more in pelvic-fin growth than recruit-spawning fish, whereas the reverse was true for farmed males. Males use pelvic fins to embrace females during ventral mounts, a key mating behaviour, and display them to other males during agonistic interactions. The drumming muscle is used by males to produce sound during courtship and aggressive displays, whereas females only use sound outside the spawning season, for agonistic and defensive behaviours that are unlikely to be as important in the farming environment. The results are discussed in the context of the reproductive success of farmed escapees in the wild.